P1147Complications in young ICD patients - a retrospective analysis. (18th June 2020) - Zweiker, D; Puntus, T; Egger, F; Kriz, R; Koch, J; Hellebart, P; Huber, K; Nurnberg, M
Abstract: Introduction: In specific situations implantable cardioverter defibrillator (ICD) therapy is recommended for patients under the age of 40 years. Due to the active lifestyle of this patient population, complication rates in devices with conventional transvenous electrodes may be higher than for the remaining population. Methods: The ICD-YOUNG study is a retrospective analysis of consecutive patients ≤ 40 years undergoing transvenous or subcutaneous ICD (s-ICD) implantation, device change or lead revision at our centre between July 2006 and December 2017. Rehospitalization for lead failure or device battery depletion was documented. Results: Out of 586 patients undergoing ICD implantation, 35 patients (6.0%) were ≤ 40 years. Mean age was 30.0 ± 7.2 years, 48.6% were female, 37.1% received ICD therapy for primary prevention and 11.4% primarily received s-ICD. Median follow up was 7.3 (interquartile range, 1.8-12.0) years, with a lower follow up duration in s-ICD patients than conventional ICD patients (median, 2.9 vs. 9.0 years). Over the course of follow-up, 37.1% received successful anti-tachycardia therapy. 19.4% of patients in the conventional ICD group had right ventricular lead problems requiring intervention, while none of the s-ICD patients had to be revised. Time to first device change due to battery depletion and/or device upgrade was similar in young and remaining patients (median 5.4 vs 6.0 years, p = 0.23). Discussion: Young patients requiring ICD have a high rate of lead problems. In most young patients, s-ICD therapy is an encouraging alternative to conventional ICD therapy with a lower lead failure rate.